The efficacy of hemostatic radiotherapy for bladder cancer-related hematuria in patients unfit for surgery - E. Lacarriere; C. Smaali; A. Benyoucef; C. Pfister; P. Grise (International Brazilian Journal of Urology, 2013)
Objective The aim of our study was to assess short and mid-term clinical efficacy of external beam radiation therapy to achieve hemostasis in patients with bladder-cancer related gross hematuria who were unfit for surgery. We also assessed hypofractionation as a possible alternative option for more severe patients. Patients and Methods Thirty-two patients were included for hemostatic radiation therapy, with two schedules based on Eastern Cooperative Oncology Group performance status. The standard treatment was 30 Gy in 10 fractions over 2 weeks. More severe patients underwent a hypofractionated regimen, with 20 Gy in 5 fractions over a one week period. Clinical evaluation was performed at 2 weeks and 6 months. Results At 2 weeks, 69% of patients were hematuria-free. Subgroup analysis showed that 79% of patients undergoing hypofractionated regimen were hematuria-free. A total of 54% were hematuria-free with the standard regimen. Based on tumor stage, hematuria was controlled at 2 weeks for 57% of non-muscle invasive tumors and 72% of muscle-invasive tumors. After 6 months, 69% of patients had relapsed, regardless of tumor stage or therapy schedules. Conclusions Hemostatic radiotherapy is an effective option for palliative-care hematuria related to bladder cancer in patients unfit for surgery. Although it appears to be rapidly effective, its effect is of limited duration. Hypofractionation also seems to be an effective option; however larger cohorts and prospective trials are needed to evaluate its efficacy compared to standard schedules.